Strategi pembangunan Kawasan Ekonomi Khusus (KEK) Sulawesi Tenggara: Kajian potensi daerah berbasis sektor unggulan - Halik, Faturrohman Muhammad (Nur Science Institute, 2025)
The development of regional economic potential plays a strategic role in supporting national growth, particularly through Kawasan Ekonomi Khusus (KEK). Southeast Sulawesi, as part of the Sulawesi Economic Corridor under Indonesia’s Masterplan for Acceleration and Expansion of Economic Development (MP3EI), has been designated as a